Social media and suicide prevention: a systematic review. Issue 2 (19th February 2015) - Robinson, Jo; Cox, Georgina; Bailey, Eleanor; Hetrick, Sarah; Rodrigues, Maria; Fisher, Steve; Herrman, Helen
Abstract: Aim: Social media platforms are commonly used for the expression of suicidal thoughts and feelings, particularly by young people. Despite this, little is known about the ways in which social media can be used for suicide prevention. The aim of this study was to conduct a systematic review to identify current evidence pertaining to the ways in which social media are currently used as a tool for suicide prevention. Methods: Medline, PsycInfo, Embase, CINHAL and the Cochrane Library were searched for articles published between 1991 and April 2014. English language articles with a focus on suicide‐related behaviour and social media were included. No exclusion was placed on study design. Results: Thirty studies were included; 4 described the development of social media sites designed for suicide prevention, 6 examined the potential of social media in terms of its ability to reach or identify people at risk of suicide, 15 examined the ways in which people used social media for suicide prevention‐related purposes, and 5 examined the experiences of people who had used social media sites for suicide prevention purposes. No intervention studies were identified. Conclusion: Social media platforms can reach large numbers of otherwise hard‐to‐engage individuals, may allow others to intervene following an expression of suicidal ideation online, and provide an anonymous, accessible and non‐judgmental forum for sharing experiences. Challenges include difficulties controlling user behaviour and accurately assessing risk, issues relating to privacy and confidentiality and the possibility of contagion. Social media appears to hold significant potential for suicide prevention; however, additional research into its safety and efficacy is required.